Relationship Of School Operational Assistance And Teaching Supervision Implementation With The Performance Teachers In Madrasah Ibtidaiyah Simalungun District - Edi Saputra, Madar Zuabi (LPPPIPublishing, 2021)
This study seeks to find out how the relationship between the financing of School Operational Assistance and Supervision on improving the performance of State Madrasah Ibtidaiyah teachers in Simalungun Regency. This research was conducted in Madrasah Ibtidaiyah Negeri Simalungun Regency, with the teacher as the research subject. This research is descriptive-inferential while the results of the study There is a significant relationship between the Financing of School Operational Assistance (X1) on the Performance of Madrasah Ibtidaiyah Teachers in Simalungun Regency (Y) with an effective contribution of 14.77%. There is a significant relationship between the implementation of teaching supervision (X2) on the performance of Madrasah Ibtidaiyah teachers in Simalungun Regency (Y) with an effective contribution of 26.86%. There is a significant relationship between the Financing of School Operational Assistance (X1) and the Implementation of Teaching Supervision (X2) together with the Performance of Madrasah Ibtidaiyah Teachers in Simalungun Regency (Y) with an effective contribution of 41.63%.